Low semen quality and experiences of masculinity and family building. (2nd March 2018) - Sylvest, Randi; Fürbringer, Jeanette K.; Pinborg, Anja; Koert, Emily; Bogstad, Jeanette; Loessl, Kristine; Praetorius, Lisbeth; Schmidt, Lone
Abstract: Introduction: Infertility is a concern for men and women. There is limited knowledge on how male factor infertility affects the couple in fertility treatment. The aim of this study was to explore how severe male factor infertility affects men's sense of masculinity, the couple's relationship and intentions about family formation. Material and methods: Semi‐structured qualitative interview study at the Fertility Clinic at Copenhagen University Hospital, Hvidovre, Denmark. Ten men with very poor semen quality initiating fertility treatment were interviewed between November 2014 and May 2015. Data were analyzed using qualitative content analysis. Results: Three themes were identified: "Threatened masculinity", "Being the strong one: impact on the couple" and "Consideration of family building options: a chapter not willing to start". The men felt that they could not fulfill their role as a man. Some couples had conflicts and discussions because the women in general wanted to talk more about infertility than the men. The men focused on having a biological child. They wanted to focus on achieving biological parenthood and postpone consideration of other family building options such as adoption or the use of semen donation in order to become a parent. Conclusions: The consequence of severe male factor infertility was a threatened sense of masculinity. Fertility specialists and nurses should recognize the impact of male infertility and create space to give their patients an opportunity to verbalize their concerns and questions related to male factor infertility and the different challenges that the couple faces during the fertility treatment.